Polychaete (Alitta virens) meal inclusion as a dietary strategy for modulating gut microbiota of European seabass (Dicentrarchus labrax) - Monteiro, Marta; Rimoldi, Simona; Costa, Rafaela S.; Kousoulaki, Katerina; Hasan, Imam; Valente, Luisa M. P.; Terova, Genciana (Frontiers in Immunology, 2023)
Recent research has revealed the significant impact of novel feed ingredients on fish gut microbiota, affecting both the immune status and digestive performance. As a result, analyzing the microbiota modulatory capabilities may be a useful method for assessing the potential functionality of novel ingredients. Therefore, this study aimed to evaluate the effects of dietary polychaete meal (PM) from Alitta virens on the autochthonous and allochthonous gut microbiota of European seabass (Dicentrarchus labrax). Two diets were compared: a control diet with 25% fishmeal (FM) and a diet replacing 40% of fishmeal with PM, in a 13-week feeding trial with juvenile fish (initial weight of 14.5 ± 1.0 g). The feed, digesta, and mucosa-associated microbial communities in fish intestines were analyzed using high-throughput sequencing of the 16S rRNA gene on the Illumina MiSeq platform. The results of feed microbiota analyses showed that the PM10 feed exhibited a higher microbial diversity than the FM diet. However, these feed-associated microbiota differences were not mirrored in the composition of digesta and mucosal communities. Regardless of the diet, the digesta samples consistently exhibited higher species richness and diversity than the mucosa samples. Overall, digesta samples were characterized by a higher abundance of Firmicutes in PM-fed fish. In contrast, at the gut mucosa level, the relative abundances of Mycobacterium, Taeseokella and Clostridium genera were lower in the group fed the PM10 diet. Significant differences in metabolic pathways were also observed between the FM and PM10 groups in both mucosa and digesta samples. In particular, the mucosal pathways of caffeine metabolism, phenylalanine metabolism, and sulfur relay system were significantly altered by PM inclusion. The same trend was observed in the digesta valine, leucine, and isoleucine degradation and secretion pathways. These findings highlight the potential of PM as an alternative functional ingredient in aquafeeds with microbiota modulatory properties that should be further explored in the future.